2013
DOI: 10.1016/j.jsat.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Developmental timing of first drug treatment and 10-year patterns of drug use

Abstract: To examine the developmental timing of first drug treatment and its associations with 10-year drug use patterns, pooled data (N=1,318) from 4 longitudinal studies conducted in California was used to compare individuals first treated during young adulthood (26%) to those first treated at an older age. Treatment timing was associated with particular participant characteristics and experiences. Matched data showed that most people in both age groups exhibited a low level of drug use after first treatment, albeit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 83 publications
2
16
1
Order By: Relevance
“…A longitudinal study (Dennis, et al, 2005) of a large heterogeneous sample in a public treatment system found that age of first substance use, age of treatment entry and duration between the two were all independently associated with substance use and treatment careers. In the Evans et al study, a starting point for the current study, individuals first treated as young adults had higher drug use and incarceration rates over the 10-year follow-up compared with a matched sample of individuals first treated as older adults (Evans, et al, 2013). Although rates of continuing care were low among both age cohorts, receipt of more drug treatment was associated with lower levels of use among those first treated as young adults, but not among the older adults.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A longitudinal study (Dennis, et al, 2005) of a large heterogeneous sample in a public treatment system found that age of first substance use, age of treatment entry and duration between the two were all independently associated with substance use and treatment careers. In the Evans et al study, a starting point for the current study, individuals first treated as young adults had higher drug use and incarceration rates over the 10-year follow-up compared with a matched sample of individuals first treated as older adults (Evans, et al, 2013). Although rates of continuing care were low among both age cohorts, receipt of more drug treatment was associated with lower levels of use among those first treated as young adults, but not among the older adults.…”
Section: Discussionmentioning
confidence: 82%
“…Evans and colleagues (Evans, Li, Grella, Brecht, & Hser, 2013) examined the developmental timing of first drug treatment and its association with longitudinal drug use patterns. Using pooled data from four longitudinal studies (N=1318), the authors created a sample of individuals first treated either during young adulthood (26%) or at an older age, matched on demographics, primary drug type, age at first use of primary drug and age at first arrest.…”
Section: Introductionmentioning
confidence: 99%
“…All studies were conducted in California. Following our prior work with this sample (Brecht et al, 2008; Evans et al, 2013; Hser et al, 2008a, 2008b), we selected from each study those subjects who reported a primary drug problem of heroin, cocaine, or methamphetamine use. Projects included: (1) 33-year heroin follow-up study (Hser et al, 2001); cocaine treatment evaluation (Hser et al, 2006), methamphetamine natural history study (Brecht et al, 2004), treatment process study (Hser et al, 2004), and treatment utilization and effectiveness study (Hser et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Informed by the literature on the cumulative effect of drug treatment on drug use patterns (Evans et al, 2013; Hser et al, 2006; Li et al, 2010; Scott et al, 2005), two additional covariates of interest were constructed. First, indicator variables for 1 st to ≥5 th episode attempts were derived following construction of the repeated-measures dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Although the question of access to substance abuse treatment is central, it is also important to look at the specific characteristics of the youngest users (Bukstein et al, 2005;Evans et al, 2013;Gulliver et al, 2010;Hoeppner et al, 2014;Parthasarathy & Weisner, 2005;Priester et al, 2016;SchumanOlivier et al, 2014;Smith et al, 2011;Sterling et al, 2010). While older individuals may have more experience with services, fruitful or not, young users are often still unfamiliar with these settings; they can then express specific needs which, if they are met, will influence their treatment access experiences.…”
Section: Discussionmentioning
confidence: 99%